(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The article provides a philosophical analysis of the national and religious peculiarities of the ancient family rituals and customs of our ancestors. The role of this ceremony and Customs in stabilizing the family environment is shown by the important characteristics of folk medicine.